Improving the Energy Sector and Renewable Energy Resources in Egypt (Challenges, Achievements, And Most Important Projects) - O. N. Misko; A. Sh. Darwish (Управленческое консультирование)
Egypt faces a challenge in providing sufficient resources for energy needs, especially, since Egypt relies mainly on oil and natural gas to meet its energy needs, on which the percentage of dependence has reached 95% of Egypt’s total energy needs. All studies indicate that despite Egypt’s possession of reserves from these sources, due to the growing use of these resources and the high cost of extracting them, Egypt will face a deficit in covering its needs from these resources. Although it is expected that the balance between oil and gas production will return with uses within few years after overcoming the economic difficulties that faced the oil and gas sector, according to Egypt’s energy strategy for the year 2030 and its current update to reach it for the year 2035, it is expected that Egypt will become a permanent importer. Oil and gas within a period not exceeding several years from the beginning of the third decade of this century. This situation represents an additional challenge to the Egyptian economy, as it becomes exposed to price turmoil in the global energy markets, which cannot be expected or controlled. This is in addition to the drain on Egypt’s foreign exchange resources, the impact on the balance of trade, and the reduction of the competitiveness of the national economy. Therefore, the diversification of energy sources must be reconsidered in order to achieve maximum benefit from local resources, which are characterized by sustainability and stability in prices, which are features that characterize electricity production projects from renewable sources, taking into account Egypt’s richness in these resources. Therefore, Egypt has already started implementing many projects that work to provide Egypt’s energy needs, through the project of the nuclear power plant in “Al-Dabaa” in northern Egypt on the Mediterranean coast, as well as power generation projects from renewable energy sources available in Egypt, such as “wind energy” and “solar energy”.